Peran Orang Tua dalam Pelaksanaan Pembelajaran PKn dimassa Pandemi Covid 19 pada Siswa Kelas III SD Negeri 6 Dobo - Salmanu, Sara; Salamor, Lisye; Yohannes, Nathalia Y. (Universitas Pattimura, Program Studi Diluar Kampus Utama (Program Studi Pendidikan Guru Sekolah Dasar), 2022)
This study aims to determine the role of parents and inhibiting factors in the implementation of Civics learning during the Covid 19 pandemic in third grade students of SD Negeri 6 Dobo. This type of research is qualitative. The research subjects consisted of informants, namely parents of third grade students at SD Negeri 6 Dobo. The research data were analyzed descriptively and qualitatively. The results of the study showed that the parents of class III students at SD Negeri 6 Dobo fought in the implementation of Civics learning during the Covid 19 pandemic, namely: guiding children for online learning, participating in adding insight and knowledge to guide children during the online learning period, providing advice and motivation to children. during online learning, have tried to make the home environment comfortable for children's learning during online learning, have met children's learning needs, divided attention between online learning and work and took the time to accompany your children in online learning. The inhibiting factors for the role of parents of third grade students at SD Negeri 6 Dobo in the implementation of Civics learning during the Covid 19 pandemic are: parents, these difficulties are in the form of: difficulty helping children to understand the material being studied, difficulty dividing work time with online learning time and home atmosphere conditions less calmc